Correlation of technetium-99m MIBI and thallium-201 retention in solitary cold thyroid nodules with postoperative histopathology - KABASAKAL, LEVENT (SPRINGER VERLAG, 2000)
A comparative prospective study of technetium-99m methoxyisobutylisonitrile (MIBI) and thallium-201 with early (15 min) and delayed (90 min for MIBI, 3 h for Tl-201) imaging in the differentiation of thyroid lesions is presented, Forty patients with cold thyroid nodules visualised on Tc-99m-pertechnetate scan and with dyskaryotic or atypical epithelial cells verified by fine-needle aspiration biopsy underwent MIBI and Tl-201 scintigraphy at 3-day intervals. Subsequent thyroidectomies were carried out in all patients. Semiquantitative analysis was performed using a lesion to non-lesion ratio on early (ER) and delayed images (DR). Additionally, a retention index (RI) was calculated using the formula RI=(DR-ER) x 100/ER. The reproducibility of the method for the early and delayed measurements was tested by analysing intra- and inter-observer variability and repeatability coefficients. Histopathologically, the nodules were found to be well-differentiated thyroid cancer in 21 patients and benign in 19 patients. There was no significant difference in the ER between malignant and benign lesions for either Tl-201 or MIBI (P>0.05). However, for both agents significant differences were found between malignant and benign lesions with regard to DR (P<0.01 for Tl-201 and P<0.001 for MIBI) and RI (P<0.001 for both agents). Statistical comparison of the two agents showed no significant differences (P>0.05) except with regard to DR and RI in malignant nodules (P<0.05). A receiver operating characteristic analysis was performed to determine threshold levels for the differentiation of malignant from benign nodules. Following this analysis, ER, DR and RI levels of 1.03, 1.54 and 2 for MIBI and less than or equal to 1.42, 1.24 and 5 for Tl-201 were selected. Using these threshold levels, the sensitivity, specificity and accuracy of the study were 90.5%, 36.8% and 65% for ER MIBI, 61.9%, 94.7% and 77.5% for DR MIBI, 95.2%, 89.4% and 92.5% for RI MIBI, 85.7%, 47.3% and 67.5% for ER Tl-201 , 80.9%, 73.6% and 77.5% for DR Tl-201, and 90.5%, 4.7% and 92.5% for RI Tl-201. In conclusion, the DR for MIBI and Tl-201 is superior to the ER in detecting malignant nodules, and the RI for both MIBI and Tl-201 is more valuable than the DR in differentiating malignant from benign thyroid nodules.
Keywords: technetium-99m methoxyisobutylisonitrile thallium-201; thyroid nodules; DOUBLE-PHASE; CLINICAL-EVALUATION; ASPIRATION BIOPSY; TC-99M MIBI; FOLLOW-UP; TL-201; SCINTIGRAPHY; TUMOR; BENIGN; CARCINOMA